Preparation, characterization and properties of core-shell cobalt ferrite/polycaprolactone nanomagnetic biomaterials - Khoo, Kok Siong; Nur Farhana Amari,; Tan, Chun Yuan; Shahidan Radiman,; Redzuwan Yahaya,; Muhamad Samudi Yasir, (Universiti Kebangsaan Malaysia, 2013)
Combination of magnetic and biocompatible materials to form core-shell nanomaterials has been widely used in medical fields. These core-shell magnetic biomaterials have a great potential for magnetic fluid hyperthermia (MFH) treatment to remedy cancer. The aims of this study were to investigate the production of core-shell cobalt ferrite/polycaprolactone (CoFe2O4/PCL) nanomaterials with different ratios of cobalt ferrite to caprolactone, to study the effects of using polymer in reducing the agglomerations between particles and to determine the structure, morphology, thermal and magnetic properties of these core-shell nanomaterials. The core-shell nanomaterials were produced by in situ polymerization method. The formation of the CoFe2O4/PCL was investigated by means of Fourier transform infrared spectroscopy (FTIR), x-ray diffractometer (XRD) and transmission electron microscopy (TEM). Its thermal properties were determined by using thermogravimetric analyzer (TGA). The vibrating sample magnetometer (VSM) was used to reveal the magnetic properties. The results for the XRD and FTIR spectra demonstrated the formation of cobalt ferrite and polycaprolactone in core-shell nanomaterials. From the TEM results, it was seen that the core-shell CoFe2O4/PCL nanomaterials were best formed at a ratio of CoFe2O4 to monomer caprolactone mixtures of 1:4.